Colorectal multidisciplinary meeting audit to determine patient benefit. Issue 11 (3rd November 2015) - Fernando, Chris; Frizelle, Frank; Wakeman, Chris; Frampton, Chris; Robinson, Bridget
Abstract: Background: New Zealand tumour standards require discussion of all cases of colorectal cancer in a multidisciplinary meeting (MDM), but supporting evidence is lacking. The aim was to determine which patients benefit from MDM discussion. Methods: A retrospective and prospective audit was undertaken of all patients discussed in the Christchurch Hospital colorectal MDM over 12 months to November 2014, who were compared with contemporaneous patients not discussed and identified through Hospital discharge codes. Results: In total, 641 patients were identified, with 459 (70%) discussed in the MDM, on average 7 years younger than not discussed. The proportion discussed by location was 39.2% colon, 63% rectosigmoid, 98% rectal, 96.6% anal. Discussed patients were more likely to have magnetic resonance imaging (68% cf 9.3%), fluorodeoxyglucose positron emission tomography scan (18% versus 2%) and chest computerized tomography scan (50% versus 26%). For colon cancer, American Joint Committee on Cancer (AJCC) stage I and II, 91% of 68 non‐discussed patients went straight to surgery compared with 48% of 27 discussed in the MDM; for AJCC stage III uptake of adjuvant chemotherapy was the same whether discussed or not. An R0 resection was achieved for 91% of discussed patients, and 96% of not discussed. A clear referrer's plan, prospectively recorded in 94 patients, was changed after the MDM in 23%. Clinical staging was changed in 20 patients (4%), none with colon cancers. Conclusions: Discussion in the MDM influenced management, but was unlikely to change management for AJCC stage I/II colon cancer, who could be spared mandatory review in the MDM and be discussed selectively as treating clinicians decide.